PENGARUH LINGKUNGAN KERJA PERAWAT TERHADAP PELAKSANAAN PRAKTEK KEPERAWATAN DI RUMAH SAKIT UMUM Dr. SAIFUL ANWAR MALANG TAHUN 2006 - Putra, Kuswantoro Rusca; Hamid, Achir Yani S.; Mustikasari, Mustikasari (Jurnal Kedokteran Brawijaya, 2007)
The implementation of nursing practice is related tonurses' working environment. The working environment components consist of leadership, culture and management; control over workload; control over practice; and adequate source. The purpose of this study is to identify any correlation between the nurses work environment with the implementation of nursing practice. The research was conducted in IRNA(Inpatients Ward) I and of IRNA II RSU Dr. Saiful  Anwar on May 1stuntil 20th, 2006. Correlation was chosen as the research design using cross sectional study on 196 nurses with two instruments: nurses' work environment, and implementation of nursing practice. The result based on analysis with regression linier indicates that there is a significant correlation between working nurse environment(leadership, culture and management; control over workload; control overpractice; and adequate source) with the implementation of nursing practice (p < 0.05) and control over practice is the biggest sub variable that influences the implementation of nursing practice(B=1.302). In conclusion, the nurse’s working environment influences implementation of nursingpractice in hospital. Keywords:Work environment, Implementation of nursing practice